Human-sloth Bear Conflict: Causes and Mitigation in Kota, Rajasthan, India - Choudhary, Kiran; Nama, Krishnendra Singh (Indian Forester, 2018)
The sloth bear (Melursus ursinus), is the most dangerous wild animal due to its’ unpredictable behaviour and often attacks on human in forests. The present investigation represents human-sloth bear conflicts, as per standard methods and survey. The results suggested that, most of the casualties can be reduced by restricting human entries into sloth bear habitats, avoiding camping and housing in their habitats especially near water sources. Further road accidents were common in the study area due to National Highway near the forest area. The scientific management in collaboration with local inhabitants will support the conservation of this species.